FINANCIAL DIARY: A TOOL FOR FINANCIAL PRUDENCE (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2022)
Financial planning is very crucial for achieving  financial goals in life, one can anticipate the  financial needs of the future and can ensure a  smooth flow of funds at all times. The study is  an eye-opener to the respondents as they got to  know the pattern of their income and expenses.  By saving the money spent on bad habits such  as tobacco, smoking and drinking; they will be  able to divert their income to return generating  micro-investment avenues in future.
Keywords: Financial planning; LITERATURE REVIEW; emergencies